2015
DOI: 10.3233/cbm-150516
|View full text |Cite
|
Sign up to set email alerts
|

Markers of progression and invasion in short term follow up of untreated breast cancer patients

Abstract: Higher concentrations of IL-8, uPA, PAI-1 and MMP2, as is MMP9 and VEGF, confirmed aggressive phenotype and poor prognosis in different subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Carlos reported that hyaluronan promotes cancer cell migration and increases the secretion of matrix metalloproteinase, specifically the increased active form of MMP-2 28 . Several studies indicated that a high MMP-2 expression is correlated to poor prognosis in prostate cancer 11 , bladder cancer, and breast cancer 29 . In addition, MMP-2 upregulation is associated with poor prognosis in RCC patients, and thus the inhibition of MMP-2 activity can suppress cancer metastasis 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Carlos reported that hyaluronan promotes cancer cell migration and increases the secretion of matrix metalloproteinase, specifically the increased active form of MMP-2 28 . Several studies indicated that a high MMP-2 expression is correlated to poor prognosis in prostate cancer 11 , bladder cancer, and breast cancer 29 . In addition, MMP-2 upregulation is associated with poor prognosis in RCC patients, and thus the inhibition of MMP-2 activity can suppress cancer metastasis 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the IL8 (-251) A allele and/or the CXCR2 (+1208) T allele showed a significant association with decreased overall survival and decreased disease-free survival. We have recently shown the prognostic relevance of IL8 in adjuvantly untreated early breast cancer patients in short-term and long-term follow-up (Milovanović et al 2013;Abu Rabi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings confirm those of numerous other studies that have reported uPA and PAI-1 to be statistically independent prognostic factors in lymph node-negative breast cancer patients. 10 - 18 However, these studies did not include HER2 status which is now an important part of the decision about adjuvant systemic therapy. Because of the observed associations between overexpression of the HER2/ neu protein and tumor proteolytic factors in breast and in other cancers 19 - 21 , HER2/neu has been suggested to up-regulate the proteolytic enzymes, including uPA and PAI-1, and thus play a direct role in tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%